Pidana Mati bagi Koruptor: Dilema Konstitusional dalam Perspektif Pancasila dan HAM - Mokhamad Naufal Islami; Ali Masyhar Mursyid (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
Law No. 20 of 2001 has institutionalized the provision of the death penalty for corruptors under certain circumstances. This research analyzes juridically the application of the death penalty against perpetrators of corruption from a normative, positive law, ethical, and religious perspective. The method used is a normative juridical approach with secondary data. Data analysis is carried out systematically to identify themes and formulate operational hypotheses. The results showed that the death penalty in the corruption law has been regulated for certain circumstances. Still, its implementation faces constitutional challenges from three critical perspectives: the Pancasila legal state framework, the 1945 Constitution's provisions on the right to life, and human rights principles. International frameworks such as the ICCPR, various legal interpretations, and religious approaches enrich this debate. In conclusion, applying the death penalty for corruption offenders in Indonesia cannot be implemented due to constitutional dilemmas arising from these various perspectives, thus requiring reformulation and in-depth study of legal norms and human values